Exploring the value of an educational partnership within a multilingual pre-school setting - Maritz, Anneliese (Rhodes University, Faculty of Humanities, Department of Psychology)
This modest research project was situated in a multilingual Early Childhood Development (ECD) setting in the Eastern Cape (EC) province of South Africa. In the context of high levels of poverty and unemployment in the EC, issues such as under-funding, the nature of the training of practitioners, translating the importance of learning through play into practice, difficulties dealing with diverse cultural practices and the use of multiple languages, all impact ECD provision. Research has shown that parental involvement and creating parent-school partnerships can assist children to progress at school. The overall objectives of this project were to explore how a team in an ECD centre might communicate more effectively with parents and how early stimulation practices in home and school might benefit the child's development. The theoretical framework draws upon Vygotsky's (1978) socio-cultural historical theory, Bernstein's (1971) elaborated and restricted language codes and Bourdieu's (1977) concepts of social reproduction. A research project in the Netherlands Thuis in School, used an education partnership approach (Iliás et al., 2019). They developed a manual that was adapted for our local context by drawing from the theories mentioned, and to counter the dominant approaches where parenting programs have often been offered from a deficit, narrow perspective. Action Research guided the interventionist approach to workshop sessions, to enable mutual capacity-building of parents and practitioners. To ensure informed consent, participants' first languages were used. High risk factors related to photographs and videos of participating parents and minor children were successfully addressed. Pre- and post-interviews and workshop data were analysed using template analysis, within a constructivist paradigm. Findings include vignettes to introduce the contexts and parents' ideas prior to the sessions. Then, sessions are summarised as action cycles, with key participants' responses. Finally, post-session evaluations highlight the topics the parents found most meaningful; and parents' and practitioner accounts of changes in practices. This research illustrates ways that educational partnership elements can influence practice and policy, to improve home and school environments for the benefit of children.
Keywords: Early childhood education Parent participation -- South Africa -- Eastern Cape; Early childhood teachers Training of; Home and school -- South Africa -- Eastern Cape; Parent-teacher relationships -- South Africa -- Eastern Cape; Communication and education -- South Africa -- Eastern Cape